Contextual influences on health worker motivation in district hospitals in Kenya. - Mbindyo, P; Gilson, L; Blaauw, D; English, M (2009)
BACKGROUND: Organizational factors are considered to be an important influence on health workers' uptake of interventions that improve their practices. These are additionally influenced by factors operating at individual and broader health system levels. We sought to explore contextual influences on worker motivation, a factor that may modify the effect of an intervention aimed at changing clinical practices in Kenyan hospitals. METHODS: Franco LM, et al's (Health sector reform and public sector health worker motivation: a conceptual framework. Soc Sci Med. 2002, 54: 1255-66) model of motivational influences was used to frame the study Qualitative methods including individual in-depth interviews, small-group interviews and focus group discussions were used to gather data from 185 health workers during one-week visits to each of eight district hospitals. Data were collected prior to a planned intervention aiming to implement new practice guidelines and improve quality of care. Additionally, on-site observations of routine health worker behaviour in the study sites were used to inform analyses. RESULTS: Study settings are likely to have important influences on worker motivation. Effective management at hospital level may create an enabling working environment modifying the impact of resource shortfalls. Supportive leadership may foster good working relationships between cadres, improve motivation through provision of local incentives and appropriately handle workers' expectations in terms of promotions, performance appraisal processes, and good communication. Such organisational attributes may counteract de-motivating factors at a national level, such as poor schemes of service, and enhance personally motivating factors such as the desire to maintain professional standards. CONCLUSION: Motivation is likely to influence powerfully any attempts to change or improve health worker and hospital practices. Some factors influencing motivation may themselves be influenced by the processes chosen to implement change.